A decision-making model to guide securing blockchain deployments - Cronje, Gerhard Roets (Rhodes University, Faculty of Science, Department of Computer Science)
Satoshi Nakamoto, the pseudo-identity accredit with the paper that sparked the implementation of Bitcoin, is famously quoted as remarking, electronically of course, that "If you don't believe it or don't get it, I don't have time to try and convince you, sorry" (Tsapis, 2019, p. 1). What is noticeable, 12 years after the famed Satoshi paper that initiated Bitcoin (Nakamoto, 2008), is that blockchain at the very least has staying power and potentially wide application. A lesser known figure Marc Kenisberg, founder of Bitcoin Chaser which is one of the many companies formed around the Bitcoin ecosystem, summarised it well saying ""¦Blockchain is the tech - Bitcoin is merely the first mainstream manifestation of its potential" (Tsapis, 2019, p. 1). With blockchain still trying to reach its potential and still maturing on its way towards a mainstream technology the main question that arises for security professionals is how do I ensure we do it securely? This research seeks to address that question by proposing a decision-making model that can be used by a security professional to guide them through ensuring appropriate security for blockchain deployments. This research is certainly not the first attempt at discussing the security of the blockchain and will not be the last, as the technology around blockchain and distributed ledger technology is still rapidly evolving. What this research does try to achieve is not to delve into extremely specific areas of blockchain security, or get bogged down in technical details, but to provide a reference framework that aims to cover all the major areas to be considered. The approach followed was to review the literature regarding blockchain and to identify the main security areas to be addressed. It then proposes a decision-making model and tests the model against a fictitious but relevant real-world example. It concludes with learnings from this research. The reader can be the judge, but the model aims to be a practical valuable resource to be used by any security professional, to navigate the security aspects logically and understandably when being involved in a blockchain deployment. In contrast to the Satoshi quote, this research tries to convince the reader and assist him/her in understanding the security choices related to every blockchain deployment.
Keywords: Blockchains (Databases); Bitcoin; Cryptocurrencies; Distributed databases; Computer networks Security measures; Computer networks Security measures Decision making; Ethereum